Arsenite induces dysfunction of regulatory T cells through acetylation control of the Foxp3 promoter. (January 2021) - Chen, J; Jiang, J; Liu, Y; Ye, Y; Ma, Y; Cen, Y; Chen, W; Wang, S; Yang, G; Zhang, A
Arsenic is known to cause damage to the body's immune system by inducing epigenetic changes. However, the molecular mechanism of this damage remains elusive. Here, we report that arsenic disrupts the morphology of lymphocytes, decreases cell viability, and results in abnormal proportions of T lymphocyte subsets. Moreover, our results revealed that arsenic can reduce global acetylation of histone H4 at K16 (H4K16 ac) in lymphocytes via decreasing the level of males absent on the first but upregulates mRNA and protein levels of the forkhead/winged-helix box P3 ( Foxp3 ) gene by increasing the acetylation of histone H4 at K16 (H4K16) at the promoter of Foxp3. Finally, arsenic-induced dysfunction of regulatory T cells (Tregs) could be ameliorated by trichostatin A. Our research indicates that arsenic-induced immunosuppressive effect in human lymphocytes may be related to the acetylation of H4K16 at the promoter of Foxp3 and that histone deacetylase inhibitors may play a role in the prevention and treatment of immune injury caused by arsenic.